Mewujudkan Adat Cermat Aktivitas Nalar dan Estetik “WACANA” sebagai Upaya Menciptakan Ruang Minat Baca di MTs Darut Tauhid Kecamatan Torjun Kabupaten Sampang. - Muflihatul Hasanah; Desiyanto, Jatim; Laily, Rohisotul; Sultonurrohman (EDUPEDIA Publisher, 2024)
This study addresses the significance of reading in human life, emphasizing its role in acquiring knowledge, information, and entertainment. Reading is a communicative process used by individuals to convey messages and communicate meanings. The benefits of reading include enhancing knowledge, developing critical thinking, improving brain memory, and fostering understanding. The school library is crucial in supporting the learning process by providing diverse information sources and promoting collaboration among students. Establishing reading corners or libraries within schools is an initiative to support the government's mandatory reading movement. The proposed solution, WACANA program, focuses on creating comfortable and attractive reading spaces to enhance students' reading interest. The program not only aims to establish reading corners but also provides sustainable reading facilities. This initiative targets schools lacking reading corners or libraries, with the primary goal of improving reading quality and knowledge acquisition among students. The program is set to be implemented over one month in MTs Darut Tauhid, Torjun District, Sampang Regency. The method involves several stages: preparation, implementation, mentoring, and evaluation. Activities include identifying and selecting the educational institution, program socialization, decoration planning, reading corner renovation, and the official launching of the reading corner. The main targets are increased reading interest, enhanced literacy skills, and improved education quality.